Consumer Ethnocentrism in Product Evaluation: The case of Iceland - Snorri Valur Steindórsson 1981- (2011)
There has been very little discussion in Iceland whether consumers are more favorable towards domestic made products, rather than imported. The concept Country of Origin (COO) has been studied widely for years in other countries. From the literature review, it was apparent that COO, Country´s image and ethnocentrism does influence consumers evaluation of products and it varies between low and high involvement products. This study aims to explore if there is a significant effectt of consumer ethnocentrism in product evalation in Iceland.